2020
DOI: 10.1007/s42452-020-2995-6
|View full text |Cite
|
Sign up to set email alerts
|

Model for the static friction coefficient of spherical contact with a soft metal coating

Abstract: An elastic-plastic spherical contact with soft metallic coating under combined normal and tangential loading is studied by finite element analysis. Full-stick contact condition is assumed and sliding inception is related to vanishing tangential stiffness of the contact junction. Previously observed, both experimentally and theoretically, effects of increasing coating thickness on static friction coefficient that were published in the literature are thoroughly explained here, to the authors' best knowledge, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Similar effect of coating thickness on surface friction has been reported in experimental studies for indium coated tool steel surface [46] and silver-coated hardened M2 steel surface [47]. The µ behavior as a function of t/R in [44,45] is explained in [45] by the competition of two mechanisms. One is that a thicker soft coating decreases the tangential stiffness of the contact junction leading to decreasing µ.…”
Section: Coated Rough Surface Contactsupporting
confidence: 79%
See 4 more Smart Citations
“…Similar effect of coating thickness on surface friction has been reported in experimental studies for indium coated tool steel surface [46] and silver-coated hardened M2 steel surface [47]. The µ behavior as a function of t/R in [44,45] is explained in [45] by the competition of two mechanisms. One is that a thicker soft coating decreases the tangential stiffness of the contact junction leading to decreasing µ.…”
Section: Coated Rough Surface Contactsupporting
confidence: 79%
“…In the figure, z, d and  are the asperity height measured from the mean of the It was demonstrated in [34] that soft coatings exhibit a mirror image behavior of hard coatings in terms of the yield resistance. For the static friction coefficient, Chen [44] and Zhang et al [45] showed that the soft coatings also exhibit a mirror image behavior of hard coating (Figure 6). Hence, opposite to Figure 6, in the case of soft coatings, there exists a (t/R) m corresponding to the lowest µ For t/R < (t/R) m , µ decreases with increasing t/R.…”
Section: Coated Rough Surface Contactmentioning
confidence: 99%
See 3 more Smart Citations